ANALYSING HIGHER ORDER THINKING SKILLS ON THE COMPULSORY ENGLISH TEXTBOOK FOR TENTH GRADERS OF INDONESIAN SENIOR HIGH SCHOOLS - Andi Sukmawijaya; Wisma Yunita; Dedi Sofyan (Universitas Bengkulu, 2020)
This study aimed to ascertain proportion of Higher Order Thinking Skills (HOTS) based on the revised edition of Bloom’s Taxonomy in the language skills and language knowledge of tasks in the textbook of “Bahasa Inggris of class ten employed in senior, vocational and Islamic senior high schools published by the Ministry of Education of the republic of Indonesia and its relevancy to the 2013 curriculum. By employing a content analysis research design, this study employed content cards as the instrument for analysing the textbook, in which two techniques were used to administer the data, namely content analysis and documentation. The data were analysed qualitatively using Brookhart including compiling, disassembling, reassembling, interpreting and concluding. Results turned out that the proportion of HOTS in language skills is integrated well. In addition, the content of higher-order thinking skills in tasks of the compulsory English textbook of “Bahasa Inggris of class ten employed in senior, vocational and Islamic senior high schools” is relevant to the 2013 curriculum. It has fulfilled the standard suggested by the Decrees of the Ministry of Education. It is recommended that the teachers need to train students extensively on the implementation of the HOTS to achieve the goals targeted in the 2013 curriculum well.